ダイ 33ジ ナンキョク チイキ カンソクタイ キショウ ブモン ホウコク 1992 - 松原, 和正; マツバラ, カズマサ; 小城, 良友; コジョウ, ヨシトモ; 岸, 隆幸; キシ, タカユキ; 五十嵐, 寛; イガラシ, ヒロシ; 東島, 圭志郎; ヒガシジマ, ケイシロウ; MATSUHARA, Kazumasa; KOJO, Yoshitomo; et al. (1995)
P(論文) この報告は第33次南極地域観測隊気象部門が, 1992年2月1日から1993年1月31日まで昭和基地において行った気象観測結果をまとめたものである。観測方法, 設備, 結果の取扱い等は, 第32次観測隊とほぼ同じである。越冬期間中特記される気象現象としては, 次のものがあげられる。1)ブリザードの襲来は28回, 日数では60日でほぼ平年並みであったが, 継続時間が100時間を越えるブリザードが2回あった。2)期間中, 強風や曇天の日が多く, 年平均の風速(7.1m/s), 蒸気圧(2.4hPa), 雲量(7.5)は, それぞれ強い値, 高い値, 多い値で過去の記録値を更新した。3)4年連続でオゾンホールを観測し, オゾン全量値の日別値では10月4日の140m atm-cm, 月平均値では10月の164m atm-cmが共に過去最低を記録した。 This paper describes the results of meteorological observations carried out by the Meteorological Observation Team of the 33rd Japanese Antarctic Research Expedition (JARE-33) from 1 February 1992 to 31 January 1993 at Syowa Station. The observations, instruments and statistics at Syowa Station were the same as those of the JARE-32 observation team. The principal characteristics in the period of JARE-33 are as follows : 1) Blizzards were encountered twenty-eight times spanning sixty days, both of which are normal. However, two blizzards continued over one hundred hours. 2) In most of the period of the expedition, it was cloudy and windy. Annual mean wind speed was 7.1m/s, mean vapor pressure was 2.4hPa, and mean cloud amount was 7.5. All of these values were maximum records. 3) The Antarctic ozone hole was observed for four successive years. The lowest value of daily total ozone amount was 140m atm-cm on 4 October and the lowest of monthly mean of that was 164m atm-cm in October. Both were the lowest values in the historical record. departmental bulletin paper